Growth enhancements of elevated atmospheric [CO2] are reduced under drought‐like conditions in temperate eucalypts. (21st April 2022) - Bendall, Eli R.; Bedward, Michael; Boer, Matthias; Clarke, Hamish; Collins, Luke; Leigh, Andrea; Bradstock, Ross A.
Abstract: Elevated atmospheric [CO2 ] ('eCO2 ') may alter species composition within vegetation types by favouring the growth of some species over others. However, other related changes in climate conditions, such as increased frequency and severity of drought, may reduce eCO2 fertilisation effects on plant growth. For many species, it is not known if responses will reflect variability in trait adaptations due to environment. We grew seedlings of nine species of eucalypts indicative of three regional vegetation types (representing a mesic–xeric ecosystem gradient) under two CO2 concentrations (400 parts per million; 640 ppm, i.e. eCO2 ) and two watering regimes (well‐watered; drought‐like conditions). Elevated CO2 increased biomass accumulation but drought reduced this effect, with mesic species experiencing larger relative reductions. Elevated CO2 increased the size of storage organs used during resprouting, in the absence of drought. Typical drought responses, such as increased leaf mass per unit area and root mass ratio, were more pronounced in xeric species and were reduced under eCO2 . Seedling growth and resprouting may be enhanced by eCO2, suggesting continued dominance of resprouting species in disturbance‐prone ecosystems, although severe drought is likely to offset eCO2 fertilisation. Xeric species may cope with drought more effectively under eCO2 than mesic species due to resource acquisition and storage traits that are more responsive. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.